Differential elicitation of an aspartic protease inhibitor: regulation of endogenous protease and initial events in germination in seeds of vigna radiata - Kulkarni, Aarohi; Rao, Mala (Peptides, 2009)
Plant aspartic proteases are of recent origin with their physiological significance in crucial processes emerging. Reports on the significance of aspartic protease inhibitors and their endogenous proteases in seeds of plants are scanty. This paper reports the purification of an aspartic protease inhibitor from the seeds of Vigna radiata, its control of the endogenous aspartic protease and their subsequent role in the early germination events. The role of the aspartic protease inhibitor and the enzyme in initial stages of germination of V. radiata has been tracked by differential timed expression and germination assays. The expression pattern revealed maximum expression of the inhibitor in the dormant seeds while the enzyme was predominant in the germinating seeds. Their expression patterns and interactions indicate their significance in initiation of germination. The expression of other classes of proteases was monitored during germination and a model predicting the events occurring during proteolysis of the storage protein in germination is hypothesized. The inhibitor was a linear, hydrophobic, pH stable and thermostable peptide with molecular weight of 1660 Da. The purified inhibitor showed a pI of 4.36 with the sequence as AEIYN KDGNK LDLYG. The inhibitor was found to be stable in a broad range of pH from 2 to 10 with an optimum of 3.0. The half-life of VrAPI at 100 degrees C was 30 min whereas the maximum activity was observed at 37 degrees C. The initial kinetic analysis of the inhibitor against the enclogenous protease showed an IC50 value of 11 nM while the value of the inhibition rate constant K-i was 34 x 10(-9) M. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Aspartic protease; Plant proteases; Protease inhibitors; Vigna radiata